TINGKAT POLA KONSUMSI KELUARGA PETANI NANAS DI DESA KUALU NENAS KABUPATEN KAMPAR - Fira Novianingsih; Khairani khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
The purpose of this study was to determine the level of comsumption patterns of pianeapple farmer families in the village of kualu nenas, kampar district. This type of research is a descriptive study with a quantitative approach. The population in this study were all 390 people. With a sample of 80 people. With the sampling technique method is done by incendental sampling. The result of this research is that the average income of 80 respondents is Rp. 2.269.063 and compared to the national average poverty line of Rp. 1.990.170, the pineapple farming family in kualu nenas village is in the economic welfare category or is above the poverty line. Then the average food consumption is Rp. 733.913 and non-food consumption Rp. 722.083. this means that the total expenditure for food and non-food comsumption is Rp. 1.455.994. the result of the GSR (Good service Ratio) calculation show that pineapple farmers in kualu nenas village kampar regency are economically prosperous. Because the ratio of food expentidure and non-food expentidures equal to 1.